Public Memory and Odonymics in Post-socialist Formations - Aloizou, Kyriaki (Mos Historicus: A Critical Review of European History, 2024)
The present article focuses on odonymics as representations of collective memory, as well as their transformations depending on the political and ideological context. The naming of streets and monuments is a cultural practice that normalizes the authorized version of history in the city-text and highlights the city as a place of public memory shaped by the political agendas of the elites. More specifically, during periods of socio-economic and geopolitical transformation, when mnemonic priorities change, odonymics constitute a political tool to promote and legitimize the new political and ideological canon. This article attempts to describe odonymic change as a manifestation of the redefinition of the relationship between public space and history in the context of the transition from Socialism to postsocialist formations. For this purpose, the cases of six cities (of Hungary, Poland, Romania, and the former Soviet Union) are studied, in order to highlight the removal of the socialist past from the city-text through the process of odonymic change due to its rejection by the new ideological-political reality and its replacement by new odonymics with reference mainly to the pro-socialist period.